Clustering of Slovak Sentence Melody – Methods and Results - Maria Cernanska; Ondrej Skvarek (Communications - Scientific letters of the University of Zilina, 2010)
Modern speech synthesis systems implement prosody features to achieve more naturally sounding voices, trying to produce sounds similar to the human speech. This article deals with obtaining one of prosody characteristics (sentence melody contour) from human speech recordings. Similarities of melody contours are studied using cluster analysis. Several clustering methods are evaluated for this purpose, estimation of proper number of clusters is described and typical melodies for different types of Slovak language sentences (declarative, interrogative, exclamatory, clauses with final “,” etc.) are found and recommended for implementation in our text-to-speech system.